Quantification of Riboflavin and Thiamine in GI (Geographical Indication) Branded Yogurts Collected from Bogura, Bangladesh Using HPLC Equipped with a Fluorescence Detector - Mia, Md Lemon; Sultan, Md Zakir; Ali, Md Ashraf; Simol, Hasina Akhter; Salam, Md Abdus (Bangladesh Pharmaceutical Journal, 2024)
Thiamine (vitamin B1) and riboflavin (vitamin B2) are both essential vitamins for human health. Thiamine (vitamin B1) is essential for energy metabolism, nervous system function, carbohydrate metabolism, cardiovascular health, digestion, muscle function, etc. On the other hand, Riboflavin (vitamin B2), which acts as an antioxidant, is essential for energy production, healthy skin, hair and nails, eye health, red blood cell production, nervous system function, etc. Due to its specialty, Bogura's famous yogurt was recognized as a Geographical Indication (GI) on June 26, 2023 by the Directorate of Patents, Designs, and Trademarks (DPDT) under the Ministry of Industry, the Government of the People’s Republic of Bangladesh (Prothom Alo, 2023). The purpose of the study was the quantitative determination of two water-soluble vitamins, thiamine and riboflavin, in the GI branded yogurt and whey (Ghol), collected from Bogura, Bangladesh to ensure health benefits. The methods employed for the quantitative analysis of these vitamins were reversed-phase high performance liquid chromatography (RP-HPLC) equipped with a fluorescence detector. The extraction process involved acid hydrolysis followed by enzymatic hydrolysis with takadiastase enzyme. Chromatographic separation was achieved with a Shimadzu Prominence HPLC system using isocratic elution mode on a C18 column (4.6 mm × 250 mm, 5 μm). The correlation coefficients for thiamine and riboflavin were 0.9975 and 0.9974, respectively. The recovery rates for thiamine and riboflavin were found as 97.70% and 105.40%, respectively. Twenty-two samples were analyzed. Thiamine and riboflavin were found in the range of 0.0647 to 0.1396 mg/100 g and 0.0227 to 0.3749 mg/100 g, respectively. It can be concluded that these yogurts were rich in thiamine and riboflavin. Therefore, these yogurts are beneficial for health. Bangladesh Pharmaceutical Journal 27(1): 59-66, 2024 (January)